Tissue distribution of rIX‐FP after intravenous application to rodents. (25th October 2020) - Herrmann, Sabrina; Doerr, Baerbel; May, Frauke; Kuehnemuth, Benjamin; Cherpokova, Deya; Herzog, Eva; Dickneite, Gerhard; Nolte, Marc W.
Abstract: Background: Hemophilia B is caused by coagulation factor IX (FIX) deficiency. Recombinant fusion protein linking coagulation FIX with recombinant albumin (rIX‐FP; Idelvion ® ) is used for replacement therapy with an extended half‐life. A previous quantitative whole‐body autoradiography (QWBA) study investigating the biodistribution of rIX‐FP indicated equal biodistribution, but more prolonged tissue retention compared with a marketed recombinant FIX product. Objectives: To complete and confirm the QWBA study data by directly measuring rIX‐FP protein and activity levels in tissues following intravenous (i.v.) administration to normal rats and FIX‐deficient (hemophilia B) mice. Methods: After i.v. administration of rIX‐FP at a dose of 2000 IU/kg, animals were euthanized at specific time points up to 72 hours postdosing. Subsequently, plasma and various tissues, which were selected based on the previous QWBA results, were harvested and analyzed for FIX antigen levels using an ELISA (both species) or an immunohistochemistry method (mice only), as well as for FIX activity levels (mice only) using a chromogenic assay. Results: In rats, rIX‐FP distributed extravascularly into all tissues analyzed (ie, liver, kidney, skin and knee) with peak antigen levels reached between 1 and 7 hours postdosing. In hemophilia B mice, rIX‐FP tissue distribution was comparable to rats. FIX antigen levels correlated well with FIX activity readouts. Conclusions: Our results confirm QWBA data showing that rIX‐FP distributes into relevant target tissues. Importantly, it was demonstrated that rIX‐FP available in tissues retains its functional activity and can thus facilitate its therapeutic activity at sites of potential injury.